Can APPealing and more informative bills "nudge" individuals into conserving electricity? - Lukas Meub; Petrik Runst; Kaja von der Leyen (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2019)
We use a field experiment on energy billing in a German region to evaluate the effect of two behavioral nudges (consumption feedback and social comparison) on electricity consumption. Similar experiments have revealed significant treatment effects, yet theindividual variance has proven to be substantial. On grounds of these heterogeneous treatment effects and the possibility of cross-country behavioral differences, additional experiments are warranted. For our German participants with low pre-treatment consumption compared to many other countries, we find no treatment effects. From this, we deduce that the effect of consumption feedback and social comparison is highly context dependent.
Keywords: K32; P18; Q58; 330; Energy consumtion; Electricity; Consumtion feedback